(untitled) (CIPEEX, 2025)
USE OF SUPPLEMENTS AND HERBAL MEDICINES WITHOUT A PROFESSIONAL PRESCRIPTION Wellington Henrique de Abreu¹, Teacher Barbara Martins Vieira² Universidade Evangélica de Goiás – UniEVANGÉLICA¹,² ABSTRACT In pursuit of an aesthetic social standard and better physical performance, people are searching for resources to meet their goals as quickly as possible, highlighting the use of supplements and herbal medicines. These compounds are characterized by their formulation based on vitamins, minerals, herbs, botanicals, extracts, amino acids or combinations of the items mentioned, which can be found in health food stores, supplement stores, pharmacies and even gyms. The formulations can be presented in liquid, powder, gel and capsule form and can be purchased without a medical or nutritional prescription, making it easy for people of all age groups and both sexes to consume them. The social and media pressure to reach a perfect body, the popularity and demand for supplements are increasing. As phytotherapics doesn’t have a notable toxic profile, they are often associated with medication and have a much more alarming appearance, where using them in an indiscriminating way can lead to bad effects and the possibility of not achieving the desired goal. Self-supplementation is a very common habit, since there is almost no need for a professional prescription. To this study, three articles were selected on herbal supplements and the risks associated with their use without a medical or nutritional recommendation. The three studies highlight the fact that the use of products without proper guidance can cause mild damage such as drowsiness, headaches and nausea, as well as more serious damage such as constipation, allergic reactions, intoxication, addiction and some others. It’s not good to seek for a healthier life by avoiding diseases caused by being overweight or even by a sedentary routine using supplements or herbal medicines inappropriately, leading to other types of problems or diseases and perhaps in more serious situations where extravagant dosages are used, leading to death.